Pengaruh Sikap YOLO (You Only Live Once) terhadap Perilaku Bullying pada Remaja Awal di Kota Manado - M.Tiwa, Tellma; Siregar, Dina Mariana (Jurnal Ilmiah Wahana Pendidikan, 2025)
The You Only Live Once (YOLO) phenomenon has become increasingly popular among adolescents, reflecting a lifestyle that emphasizes freedom, pleasure, and risk-taking without considering long-term consequences. When not accompanied by adequate self-control and moral awareness, this attitude may influence adolescents’ social behaviors, including bullying tendencies. This study aims to examine the effect of the YOLO attitude on bullying behavior among early adolescents in Manado City. The research employed a quantitative correlational design. The population consisted of junior high school students aged 12–15 years, with a total of 80 participants selected through purposive sampling. Data were collected using the YOLO Attitude Scale and the Bullying Behavior Scale, both of which were tested for validity and reliability. The normality test indicated a normal data distribution (Kolmogorov-Smirnov Z = 0.077; p = 0.200). The results of a simple linear regression analysis revealed a significant effect of the YOLO attitude on bullying behavior (F = 40.104; p = 0.000). The coefficient of determination (R² = 0.630) indicated that YOLO attitude contributed 63% to bullying behavior, while 37% was influenced by other factors. These findings suggest that the higher the YOLO attitude, the greater the tendency toward bullying. Therefore, character education and moral reinforcement are essential to ensure YOLO values are interpreted positively.